The carrot principle : how the best managers use recognition to engage their people, retain talent, and accelerate performance - Gostick, Adrian Robert; Elton, Chester (New York : Free Press, 2007)
Esta obra excepcional presenta los pasos simples para convertirse en un gerente de zanahoria y para crear una cultura de reconocimiento en su organización, ofrece una gran cantidad de ejemplos específicos extraídos de la vida real. --
Part I. The accelerator : how the best managers deliver extraordinary results. A missing ingredient ; The Basic Four of leadership ; Leadership accelerated ; Altruists and Expectors -- Part II. Carrot culture : how great organizations create world-class results. Creating a carrot culture ; Are they engaged and satisfied? ; The building blocks of a carrot culture ; Carrotphobia : why we don't recognize -- Part III: Managing by carrots : you can get there from here. The carrot calculator ; 125 recognition ideas -- Conclusion: Sustaining the carrot principle.
National Bestseller.
Basado en un estudio de 10 años de 200,000 gerentes y empleados.
Contiene datos biográficos de los autores en la solapa posterior.
Incluye índice.
Bibliogrrafía: páginas 197-202.
Keywords: INCENTIVOS EN LA INDUSTRIA; MOTIVACION DEL EMPLEADO; MOTIVACION PARA EL RENDIMIENTO; RENDIMIENTO LABORAL